2019
DOI: 10.1007/s11750-019-00504-6
|View full text |Cite
|
Sign up to set email alerts
|

Market share and performance in Taiwanese banks: min/max SBM DEA

Abstract: This research used a min/max slacks-based measure data envelopment analysis (SBM DEA) to explore the operational efficiency of 37 banks in Taiwan from 2012 to 2016, with the main research goals being to analyze bank efficiency, compare the differences in the average efficiency values of two models, and identify the need for improvements in the inputs and outputs, from which it was found: (1) the average efficiency of the SBM-max model for each year was higher than the SBM-min model. (2) The best input performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Following Li et al, (2019), this study adopts the approach of estimating mean factor efficiency to identify causes of inefficiency occurring in the inefficient banks. The improvement for individual input and output variable is estimated by exercising the relationship between actual and predicted estimates of the variables.…”
Section: Results and Findingsmentioning
confidence: 99%
“…Following Li et al, (2019), this study adopts the approach of estimating mean factor efficiency to identify causes of inefficiency occurring in the inefficient banks. The improvement for individual input and output variable is estimated by exercising the relationship between actual and predicted estimates of the variables.…”
Section: Results and Findingsmentioning
confidence: 99%
“…USBM DEA model permits further analysis of inefficiency existing within the banks. The relationship between projected and actual factor value can be used to estimate mean factor efficiency, which is another form to analyse the slacks present in inefficient banks (Li et al, 2019). For input mean factor efficiency index, the predicted factor value is divided by actual factor value.…”
Section: Results Analysismentioning
confidence: 99%
“…Excessive use of deposit (input variable) is another cause of inefficiency. However, Li et al (2019) found a contradictory result by proving excess deposit to be the most effective variable for Taiwanese banks. Including NPL as undesirable output in non-radial DEA model, the findings reveal that excessive level of NPLs leads to lower operational efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Data Envelopment Analysis (DEA) has become a widely used technique to compare the efficiency of serviceproducing units because it easily handles the multiple outputs characteristic of public sector production, is nonparametric and does not require input price data [34]. The popular application is with deterministic information and classic DEA models [3,10], for instance, in health care Jesús A. Tapia jesus.tapia@uva.es Bonifacio Salvador bosal@eio.uva.es 1 Department of Statistic and Operative Research, University of Valladolid, Campus Miguel, Delibes, Paseo Belén, n o ¯7,47011 Valladolid, Spain [1,37] or [25]), universities and research institutes [26], government [17], public libraries [22,23], schools [35], public transport services [15] or banks [28].…”
Section: Introductionmentioning
confidence: 99%
“…These intervals capture the random variations introduced in the DEA analysis by using outputs and inputs estimated with a sample. So far, Simar and Wilson’s [ 38 , 39 ] methodology has been the most common for measuring efficiency with bootstrap confidence intervals in such public services as health care ([ 11 ]), universities and research institutes [ 4 ], government [ 6 ], public libraries [ 29 ], schools [ 19 ], tourism [ 2 ], banks [ 28 ] or public transport services [ 21 ]. The problem posed by Simar and Wilson is different from ours because the stochastic character of the inputs and outputs is different.…”
Section: Introductionmentioning
confidence: 99%